Komunikasi Interpersonal Terhadap Hubungan Jarak Jauh pada Mahasiswa Kuliah Kerja Nyata - Aditya Lukman (Balance: Media Informasi Akuntansi dan Keuangan, 2024)
It cannot be denied that interpersonal communication is the most important foundation in learning to promote romantic relationships, especially for couples in long-term long distance relationships (LDR) who usually have open, honest and mutually supportive communication. Moreover, for couples who are dating, fulfilling obligations related to completing Real Work Study (KKN) has significant differences in challenges starting from the environment, speed, other parties involved in creating an LDR relationship plus unique phenomena such as love of place. The aim of this research is to find out how the communication that occurs between couples during this time directs long distance relationships to real work (KKN) maintaining harmonious relationships and avoiding various conflicts. Learn to use qualitative research methods, phenomenological interpretive paradigms and approaches and data collection techniques, namely. deep interview. The theory is the relationship maintenance theory used in this research and a relational dialectic theory.